(untitled) (Bangladesh Journal of Public Administration, 2022)
Most of the poultry farms in Bangladesh use antibiotics to combat the risk of disease occurrences due to poor managemental practices. This haphazard and illegitimate use of antibiotics is responsible for antibiotic resistance and residual problem in eggs and poultry meat. However, data on antibiotic consumption by layer birds and farmers’ perspectives are shockingly rare in Bangladesh. In order to understand farmers’ perceptions and antibiotic usage in Bangladesh’s small-scale layer farms, this study was performed. The research has been completed through a quantitative approach. A questionnaire survey with 20 small-scale layer farms was performed in Kamarkhanda Upazila of Sirajganj district, Bangladesh. Data has been collected and examined on farmers’ educational status, farm management, egg management, antibiotic usage and factors responsible for it. We found that 95% of farmers do not follow the drug withdrawal period though 75% of farmers had some idea about drug residue in meat and egg. 70%-layer farms are involved in antibiotic usage, not only therapeutic but also prophylaxis and egg production enhancement. Eight different types of antibiotics of six classes are randomly used without proper justification that can pose resistance and residual problem. Any of the farmers need to practise cleaning and disinfection of egg trays. It is a sign of poor management. Monitoring of antibiotic use and residue, application of proper biosecurity in farms, application of rules and legislation, and penalization for illegal practices should be implicated in Bangladesh to control antibiotic resistance and residue.